(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
This scientific article provides a comprehensive analysis of the role of the Latin language as a global standard in pharmaceutical prescription writing. The study examines the historical development of Latin, its contribution to the formation of universal terminology in pharmacy, and its functional significance in ensuring stability and clarity in prescription structure. Special attention is given to the advantages of Latin in standardizing drug names, dosages, pharmaceutical forms, and prescription formulas. The article also explores the modern relevance of Latin in international medical practice, highlighting its application in pharmaceutical nomenclature, abbreviations, dosage indications, and professional communication among healthcare specialists. Furthermore, the role of Latin in pharmaceutical education, its contribution to the formation of professional competence, and its importance in preventing clinical errors are thoroughly discussed. The findings demonstrate that Latin remains a stable and globally recognized standard in pharmacy and medicine, ensuring terminological consistency, precision, and universal understanding in pharmaceutical documentation.